2006
DOI: 10.1539/joh.48.145
|View full text |Cite
|
Sign up to set email alerts
|

Help‐Seeking in the Norwegian Police Service

Abstract: Help-Seeking in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 33 publications
10
49
1
1
Order By: Relevance
“…The present paper is part of the first comprehensive, nationwide, cross-sectional study to attempt to gather knowledge about some of these issues in the police service. Three previous articles on the basis of the present cohort have been published so far [16-18], but there is no overlap between the data presented in this paper and the previous published articles.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The present paper is part of the first comprehensive, nationwide, cross-sectional study to attempt to gather knowledge about some of these issues in the police service. Three previous articles on the basis of the present cohort have been published so far [16-18], but there is no overlap between the data presented in this paper and the previous published articles.…”
Section: Introductionmentioning
confidence: 63%
“…Data were collected by means of overlapping questionnaires. Out of 16 different questionnaires, each physician received one primary questionnaire (response rate 71.8%, N = 6,652) and three randomly selected secondary ones [18]. In the present study, comparisons are made on subjective health complaints from the primary questionnaire, whereas personality traits (response 896 physicians, 72.9%) and burnout (response 1,082 physicians, 73.3%) were from the additional questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Attitudes may prevent employees from seeking help for these problems from OHS. In a study of the Norwegian Police Force, GPs were contacted more than OH practitioners, and this was assumed to be due to availability, mistrust, and concern about anonymity [8]. However in Finland, patient satisfaction with OH physician services has been good and contacting OH physicians is more common than contacting GPs [5,23].…”
Section: Discussionmentioning
confidence: 99%
“…Dutch studies have shown that health problems and physical work demands are associated with visiting OH physicians, and that fatigue-related visits to OH physicians are more common than those to general practitioners (GP) [6,7]. In a Norwegian study, subjective health complaints and sick leave during the previous year were associated with contacting OH practitioners [8]. In addition, mental and musculoskeletal diseases are most often regarded as being possibly related to work by employees visiting OH physicians [9].…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al 28) developed and evaluated a general model of information-seeking behavior, based particularly on the stress-coping theory 29) and the riskreward theory 30) . This frequently cited model includes numerous factors that can motivate or hinder the information search, including cognitions, beliefs, attitudes, emotions, the social environment, self-efficacy and such background characteristics as gender, age and educational level [31][32][33][34][35] .…”
Section: Stage 2 − Seeking Finding and Selecting Informationmentioning
confidence: 99%